2020
DOI: 10.1186/s12937-020-00643-8
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum L.): a potential unique therapeutic food rich in organosulfur and flavonoid compounds to fight with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is the current major health crisis in the world. A successful strategy to combat the COVID-19 pandemic is the improvement of nutritional pattern. Garlic is one of the most efficient natural antibiotics against the wide spectrum of viruses and bacteria. Organosulfur (e.g., allicin and alliin) and flavonoid (e.g., quercetin) compounds are responsible for immunomodulatory effects of this healthy spice. The viral replication process is accelerated with the main structural protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 8 publications
0
58
0
6
Order By: Relevance
“…Organosulfurs and flavonoids are found to be the predominant bioactives behind the immunomodulatory nature of Allium sativum. By forming the hydrogen bonds with the active sites of serine protease these bioactives may inhibit the COVID-19 outbreak [113]. Furthermore, a study demonstrated that alliin, SAC and other bioactive compounds of Allium sativum, can be employed as a potential inhibitor candidate for COVID-19 and could be beneficial in combating this pandemic [114].…”
Section: Anti-viral Potential Of Allium Sativummentioning
confidence: 99%
“…Organosulfurs and flavonoids are found to be the predominant bioactives behind the immunomodulatory nature of Allium sativum. By forming the hydrogen bonds with the active sites of serine protease these bioactives may inhibit the COVID-19 outbreak [113]. Furthermore, a study demonstrated that alliin, SAC and other bioactive compounds of Allium sativum, can be employed as a potential inhibitor candidate for COVID-19 and could be beneficial in combating this pandemic [114].…”
Section: Anti-viral Potential Of Allium Sativummentioning
confidence: 99%
“…Laranja Excesso de frutose, que é convertido em gordura pelo fígado, a qual pode se acumular nas artérias e ocasionar problemas cardíacos, além de problemas estomacais, como úlceras. Não obstante, o problema maior das fake news estudadas se refere à substituição dos fármacos que realmente tratam os sintomas da doença pelos chamados remédios caseiros, que apenas têm efeitos auxiliares (KHUBBER et al, 2020;SILVA et al, 2020).…”
Section: Efeitos Adversos Fonteunclassified
“…Conforme descrito por Galhardi e colaboradores (2020), tal disseminação de fake news contribui para o descrédito da ciência e das instituições globais de saúde em favor do achismo. De fato, entre as principais fake news citadas pelos autores, temos em comum o uso do alho em água fervida, que até hoje não possui comprovação de eficácia no tratamento direto do coronavírus, servindo apenas como adjuvante ao estimular o sistema imunológico (KHUBBER et al, 2020;ROUF et al, 2020;SINGH;SAHU, 2020).…”
Section: Efeitos Adversos Fonteunclassified
“…It may attenuate immune system-related dysfunctions seen in patients with COVID-19 infection [ 64 ]. Aqueous extracts and essential oils of AS showed interaction with M pro protease of SARS-CoV-2 and reduced the rate of viral infection caused by SARS-CoV-2 [ 65 , 66 ]. The encapsulation of these active constituents by using different methods can improve their oxidative stability and bio-functionality and may offer targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%